Stability of inverse bicontinuous cubic phases in lipid-water mixtures - Schwarz, Ulrich S.; Gompper, Gerhard (Physical review letters, 2000)
We investigate the stability of seven inverse bicontinuous cubic phases [ G, D, P, C(P), S, I−WP, F−RD] in lipid-water mixtures based on a curvature model of membranes. Lipid monolayers are described by parallel surfaces to triply periodic minimal surfaces. The phase behavior is determined by the distribution of the Gaussian curvature on the minimal surface and the porosity of each structure. Only G, D, and P are found to be stable, and to coexist along a triple line. The calculated phase diagram agrees very well with experimental results for 2:1 lauric acid/DLPC.